STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF VOCABULARY QUIZ THROUGH THE SUBJECT “ENGLISH FOR CHILDREN” - Taslim Buaja; Amrin Hi Saban; Nursina Hamia (JURNAL DODOTO, 2021)
In creating a comfortable learning atmosphere, an English educator must have many strategies in teaching English. Many methods and techniques in language teaching can be implemented by an educator or instructor for making the learning proses running well as wanted. Without creating good learning, the room will be boring for the students, and they will consider that the teacher/instructor have not competence in his/her discipline. In this study, the researchers implemented a kind of technique in teaching English for the students using quiz. The result of implementation shown that the students got high motivation in learning English, and they had enthusism when implementing it, for taking them active involving themselves in the process of learning English.